Resenha do livro: "The engagement of Índia: strategies and responses" - Oliveira, Vinicius Tavares (Conjuntura Austral, 2015)
Resenha do livro: "The engagement of Índia: strategies and responses", de Ian Hall.  Washington: George Town, 2014.